Greenish-yellow emission from rare-earth free Li+ doped zinc vanadate phosphor - Vaibhav Chauhan; Pratik Deshmukh; S. Satapathy; Praveen C. Pandey (Results in Physics, 2022)
In this article, we present synthesis and spectral study of Zn(3-x)Lix(VO4)2 (x = 0, 0.01, 0.02, 0.03) samples. The orthorhombic phase of all the samples is validated by their XRD pattern. The crystallinity of Zn3(VO4)2 is improved by doping Li+ ions and is supported by the augmentation in crystallite size. The absorption band of the phosphors covers the near-UV region. The XPS analysis ascertains the V+5 oxidation state of vanadium thereby confirming the single-phase of the phosphors. The Li+ ion doping enhances the broadband excitation in the near UV region and emission band of Zn3(VO4)2 in the visible region with stokes shift of 9517.3 cm−1. The increased PL lifetime of the emission bands is observed after Li+ ion doping. The calculated activation energy of Li+ doped Zn3(VO4)2 phosphor is 0.29 eV and there is a 44% loss of emission intensity at 150 °C. Thus, with the broadband near-UV excitation and greenish-yellow emission, the Li+ doped zinc vanadate phosphor can be utilized with near-UV LED chips for the realization of white light.